ミクログリアによる神経活動依存的な細胞外ATPシグナルの制御 - 鈴木, 秀明; 田中, 謙二; 高橋, 由香里; 加藤, 総夫; 尾藤, 晴彦; 小泉, 修一; 繁冨, 英治; 池中, 一裕; 平山, 幸歩 (日本薬理学会年会要旨集, 2023)
Extracellular ATP (ATPo) is a signaling molecule involved in neurotransmission and neuron-glia signaling and is known to be involved in psychiatric and neurological disorders. However, the exact mechanism of ATP release and the responsible cells under physiological conditions are poorly understood due to the lack of understanding of the spatiotemporal dynamics of ATPo. Using a genetically encoded G protein-coupled receptor activation-based ATPo sensor called GRABATP1.0 , we imaged ATPo near astrocytes in the CA1 region of acute hippocampal slices. Electrical stimulation of the Schaffer collateral resulted in ATPo rise in astrocytes. The ATPo rise was inhibited by TTX, but still remained in the presence of D-APV/CNQX, suggesting that the source of activity-dependent ATP release could be presynaptic sites of neurons. Microglia depletion by PLX5562 prolonged the duration of ATPo rise, suggesting that microglia expressing NTPDase1 rapidly degrade ATPo. Consistently, POM1, a NTPDase inhibitor, increased stimulus-induced ATPo rise. Knockout of IP3R2, a major source of Ca2+ in astrocytes, did not alter the ATPo rise, suggesting　the minor contribution of astrocytic Ca2+ to ATPo. Overall data show that neuronal activity induces ATP release from axons or axon terminals, which is negatively regulated by microglia in physiology.